Shifting Meanings of Postmodern Human Education in the Practice of Using Jockey Services in State Universities, Surabaya City - Pangestuti, Ratna Dewi (Universitas Negeri Makassar, 2024)
The practice of jockey services normalized by the social world has harmed the essence of education, because it includes academic underground deviations. However, it is not subjective, because the structure also contributes to it. Thus, this study aims to uncover the occurrence of jockey service practices by focusing on identifying the agents and structures behind the rampant providers and users of jockey services for final year students at one of the state universities in Surabaya City with Pierre Bourdieu's social practice theory. The method used is qualitative with Pierre Bourdieu's generative structuralism approach. The results showed the involvement of structures, especially in campus regulations, while students have different distributions of habitus, capital, and arena.